Octopus-Inspired Biomimetic Annular Sealing Grooves: Design and Performance Optimization Under Extreme Conditions - Zhipeng Pan; Shijun Xu; Xiang Guan; Zhihong Wang; Zhenghai Qi; Xiangrui Ye; Jianyang Dong; Yongming Yao; Zhengzhi Mu (Biomimetics)
This study introduces an innovative annular sealing groove design inspired by the hierarchical structure of octopus suckers, addressing the limitations of conventional seals under extreme conditions in aerospace engineering. Using finite element analysis, eight bionic configurations with varying groove parameters (width, depth, number) were systematically evaluated under cryogenic (−196.25 °C) and high-pressure (2 MPa) scenarios. Results show that the optimized bionic6 configuration (seven grooves, 0.4 mm width, 0.4 mm depth) achieved a 21.71% improvement in average von Mises stress compared to the original design, demonstrating enhanced leakage resistance. Parameter interaction analysis revealed groove number as the most significant factor affecting performance, followed by width, while depth showed minimal influence. The hierarchical groove architecture effectively mimicked the multi-level sealing mechanism of octopus suckers, reducing leakage paths and improving adaptability to irregular surfaces. This work bridges biological inspiration and engineering application, providing a scalable solution for extreme environments. The identified optimal parameters lay a theoretical foundation for designing high-performance seals in aerospace, cryogenic storage, and advanced manufacturing.